Uptake of Zinc from Polluted Water by Decaying Tamrix gallica Leaves - R. Zaggout, Farid (Asian Journal of Chemistry, 2016)
Uptake of zinc ions from aqueous solutions by Tamrix gallica leaves was studied. The effect of several factors on this removal was studied including metal ions concentration: tamrix leaves concentration, pH, presence of competing ions, agitation, crushing, drying, presence of complexing agent and leaf extract. Application of Freundlich absorption isotherm on the present results has been examined and the parameters of this isotherm have been calculated. The interaction between metal ions and tramix leaves has been determined and mechanism for this interaction suggested.